Arab community perceptions and awareness of family medicine: a systematic review - Beesan Maraqa; Zaher Nazzal; Therese Zink (BJGP Open)
Background: Family medicine (FM), often known as general practice, is the foundation of sustainable and universal healthcare worldwide. As a new specialty in the Eastern Mediterranean Region (EMR), it must recruit doctors and gain public acceptability, which has traditionally favoured specialists. Aim: This research examined studies on Arab populations' attitudes towards FM to discover the barriers to creating and embracing this vital specialty. Design & setting: This review was based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and encompassed peer-reviewed articles from reputable sources such as PsycNet, Web of Science, PubMed, Embase, Scopus, and grey literature. Method: A comprehensive search was conducted across databases for peer-reviewed studies that explored Arabs' awareness, perceptions, and attitudes towards FM and physicians. Results: After a rigorous selection process, 19 studies were deemed suitable for analysis. These studies encompassed diverse participants, including medical students, physicians, patients, and the general public. The overall perception of FM was positive, but it was noted that few had direct exposure to family physicians during their medical education or in the clinical setting. Conclusion: Our review findings suggest the following five recommendations: (1) an education campaign for the general public about the role of FM; (2) increasing training capacity for family physicians; (3) early exposure to family physicians during medical school; (4) developing a process for continually improving the education and quality of family physicians; and (5) further research on the challenges to FM practice in Arab countries to understand the situation better and work toward its improvement.